Veljavnost oporoke z vidika obličnostnih zahtev - Lamovec Hren, Petra (Pravnik, 2023)
One of the fundamental principles of inheritance law is testamentary freedom, which ensures that the testator can determine the heirs and distribute most of the property as he sees fit, regardless of intestate succession. To do so, he must adhere to certain requirements regarding the content of testamentary dispositions and will formalities. According to the rule of strict compliance, only wills made in one of the legally prescribed forms are valid. Exceptionally, in some common law countries, a will that does not meet all formalities may also be valid. An exception from the strict rules is provided by the doctrine of harmless error and the doctrine of substantial compliance, which instead of forma ad valorem emphasise the testator’s true intention. The aforementioned rules are enacted in many countries and provide the courts with a starting point on which the latter can legally argue their decision. They were used both in cases in which the courts corrected mistakes regarding witnesses or signatures in written forms of the will, as well as in cases where the testator wrote the will in electronic form. The continental legal order does not have these exceptions, but doctrines, if enacted, could aid in the realisation of the testator’s true will.
Keywords: dediči; dedno pravo; dedovanje; doktrina neškodljive napake; doktrina znatne skladnosti; elektronska oporoka; obličnostne zahteve; oporoka; premoženje; stroga skladnost